Anthropophilic nature of the brown dog tick, rhipicephalus sanguineus in Ibadan, Nigeria (2001)
A case of human infestation by the brown dog tick, Rhipicephalus sanguineus (Latereille, 1806) is reported from a reclaimed area of land for human dwellings. The infestation is attributed to nonavailability of rodents, other game animals and reduced number of dogs used for gaming.